Epidemiology of acute myeloid leukemia: Recent progress and enduring challenges. (July 2019) - Shallis, Rory M.; Wang, Rong; Davidoff, Amy; Ma, Xiaomei; Zeidan, Amer M.
Abstract: Acute myeloid leukemia (AML) is a malignant disorder of the bone marrow which is characterized by the clonal expansion and differentiation arrest of myeloid progenitor cells. The age-adjusted incidence of AML is 4.3 per 100, 000 annually in the United States (US). Incidence increases with age with a median age at diagnosis of 68 years in the US. The etiology of AML is heterogeneous. In some patients, prior exposure to therapeutic, occupational or environmental DNA-damaging agents is implicated, but most cases of AML remain without a clear etiology. AML is the most common form of acute leukemia in adults and has the shortest survival (5-year survival = 24%). Curative therapies, including intensive chemotherapy and allogeneic stem cell transplantation, are generally applicable to a minority of patients who are younger and fit, while most older individuals exhibit poor prognosis and survival. Differences in patient outcomes are influenced by disease characteristics, access to care including active therapies and supportive care, and other factors. After many years without therapeutic advances, several new therapies have been approved and are expected to impact patient outcomes, especially for older patients and those with refractory disease.